Rail demand management: a rapid systematic review - Mohd Mahudin, Nor Diana (2014)
Train overcrowding has been associated with a number of negative outcomes, including psychological and physiological stress, negative health effects and behavioural reactions, as well as spillover effects. Despite the widely admitted seriousness of this issue, there is little agreement on the appropriate measures to deal with the increasing passenger numbers, particularly on rail services in Malaysia. This disagreement necessitates a closer scrutiny of evidence in relation to demand management strategies in the rail industry. A rapid systematic review was thus undertaken to appraise the evidence on previous and existing measures demand management strategies in rail passenger services. A total of 16 relevant studies that met the inclusion criteria were identified by a structured search of nine electronic databases. From the review, eight categories of strategies or approaches are possible in managing peak demand. These include approaches that focus on pricing, quality of service, management, policy, education, communication, engineering / design, and infrastructure. Identified key issues that presented barriers to successful implementation of these strategies are continued passenger growth, inflexibility of office hours, challenges in determining appropriate fare structures, and changing passengers’ ingrained travel behaviours. The review provides a solid basis for the more detailed discussion on the development of a structured and comprehensive demand management strategies and approaches.